Enhancing Public Health Emergency Preparedness for Special Needs Populations A Toolkit for State and Local Planning and Response - Ringel, Jeanne S. (RAND Corporation, 2009)
Experiences from Hurricanes Katrina and Rita showed that current emergency preparedness plans are inadequate to address the unique issues of special needs populations. This toolkit distills the most relevant emergency preparedness strategies, practices, and resources for these populations. It includes a Web-based Geographic Information Systems tool to identify and enumerate those with special needs in communities across the United States.